Screening Posthuman Procreation and Monstrous Motherhood in Raised by Wolves - Burnikel, Jana-Katharina (Journal of Posthumanism, 2024)
Representations of posthuman birthing and artificial motherhood are at the center of the fictional universe of the HBO sci-fi series Raised by Wolves (2020-2022). This paper investigates how the series’ cinematographic aesthetics fabricate discourses on human procreation, posthuman motherhood and maternal heteronormativity. In the series, these topics are negotiated within the categoric triangle of woman, animal, and machine. Embodied by the series’ gynoid protagonist ‘Mother’, these categories become blended into a monstrous-feminine other whose uncanny performances of maternity outline the potential fascination and horror of (post)human gestation.